Identifying the Barriers to Change in the UK Housebuilding Industry. Issue 1 (6th June 2018) - Siebert, Michael; Rodrigues, Lucelia; Gillott, Mark; Hines, Emma; Rich, David
In the UK, the sustainability agenda for housebuilding is now over ten years old, dating from the 2006 launch of the Code for Sustainable Homes as the benchmark for the reduction of carbon emissions in all new housing. The government's 2015 decision however, to dismantle the Code for Sustainable Homes and remove the 2016 Zero Carbon targets, has meant that with little warning, the sustainability industry has had to start fending for itself. Without the incentive of tariffs to focus the minds of the developers, the sustainability industry is now looking vulnerable, and the realities of having to be financially viable are coming home to roost. But our statutory requirement to reach an 80% carbon reduction by 2050 has not changed, and neither have the reasons for achieving it. During that time, the sustainability agenda was a key driver for innovation within the housebuilding industry. However, rather than focusing on the many benefits that innovation can bring, in this paper the authors look at the barriers to adoption of innovation and asks whether these barriers have been fully understood by those who are accusing the housing industry of complacency for its failure to reinvent itself. The main method used for investigating what these barriers might be was a series of industry interviews, carried out across all the sectors defined as being part of that decision-making process, in order to better understand how their motivations might differ, and if so whether this disconnect could be preventing the progress that all individually profess to want but none appear able to deliver. The findings suggest that a more informed approach to promoting or considering any innovative product within the housebuilding industry could avoid many of the barriers currently being confronted head on.